A Sustainable Approach for the Production of Green Energy With the Holistic Treatment of Wastewater Through Microbial Electrochemical Technologies: A Review - Das, Swati; Raj, Rishabh; Das, Sovik; Ghangrekar, Makarand M. (Frontiers in Sustainability, 2021)
With the plausible depletion of fossil fuels in the near future and its associated environmental impacts, researchers have instigated the search for eco-friendly renewable bioenergy. Moreover, the increase in water pollution by industrial and anthropogenic activities is another alarming global concern. In this regard, the production of renewable and sustainable green bioenergy utilizing wastewater through microbial electrochemical technologies (METs) can alleviate these crucial problems by providing a sustainable solution to meet both the demands of energy and fresh water supply. Moreover, different bio-centred techniques such as nitrification and denitrification for nitrogen removal, and elimination of carcinogenic metals, pathogens and organic components utilizing microbiota followed by toxicity sensing of different pollutants have been efficaciously exhibited through METs. However, inferior bioenergy production and recovery of low biomass yield in METs with high operational cost are noteworthy bottlenecks that hinder the scalability of this technology. Therefore, this review elaborates different physicochemical factors affecting the performance of METs, microbial interaction for the development of stable biofilm and so forth. Moreover, a broad overview on the production of bioenergy, along with the removal of pollutants from wastewater through different types of METs are also highlighted. Furthermore, the production of biofuels like ethanol, methanol, biodiesel, and gaseous fuel like bio-H2 coupled with power generation using photosynthetic microorganisms via CO2 sequestration through METs are also discussed. Additionally, recent developments with future scope for the field-scale implementation of METs along with their bottlenecks have been discussed, which has not been critically reviewed till date.